Complexation Ability of Dibenzo-24-crown-8 with Cs+ Cation in Binary Mixed Non-Aqueous Solvents - HOSSEIN ROUNAGHI, GHOLAM; MOHAJERI, MASSOUMEH; TARAHOMI, SOMAYEH (Asian Journal of Chemistry, 2010)
The complexation reaction of macrocyclic ligand, dibenzo-24- crown-8 (DB24C8) with Cs+ cation was studied in acetonitrile-methanol (AN-MeOH), acetonitrile-ethanol (AN-EtOH), acetonitrile-dimethylformamide (AN-DMF) and nitromethane-methanol (NM-MeOH) binary mixtures at different temperatures using the conductometric method. The conductance data show that in all the solvent systems, the stoichiometry of the complex formed between DB24C8 and Cs+ cation is 1:1 (ML). It was found that the stability of (DB24C8.Cs)+ complex decreases with increasing temperature. The stability constant of the resulting 1:1 complex in pure non-aqueous solvents decreases in the order: EtOH > MeOH > DMF and in binary mixed solutions, it follows the order: ANEtOH > AN-MeOH > AN-DMF. A non-linear behaviour was observed for changes of log Kf of (DB24C8.Cs)+ complex versus the composition of the binary mixed solvents. The obtained results show that the stability of the complex is quite sensitive to the composition of the mixed solvents. The values of thermodynamic quantities (ΔHºc and ΔSºc) for formation of (DB24C8.Cs)+ complex were obtained from temperature dependence of the stability constant using the van't Hoff plots. The results show that in all cases the complex is enthalpy stabilized but, in most cases entropy destabilized and both parameters are affected by the nature and composition of the mixed solvents.